Biomechanical evaluation of handgrips for the design of elbow crutches. - Comin M; Puente RP; Lois JMB; Ruiz CR; Peris JL; Sanchez-Lacuesta J; Gracia CS (Technology & Disability, 1999)
Biomechanical techniques can play a major role in the objective evaluation of technical aids performance. Little information exists regarding elbow crutch handgrip performance. This paper applies different biomechanical techniques to evaluate handgrip performance. These techniques include quantitative recording of pressures in the hand-handgrip interface, and subjective tests which, properly treated, provide objective information about the evolution of pain and general comfort in different parts of the hand, together with the user's opinion of different designs. The present work shows an application of biomechanical techniques to the design of a new handgrip for elbow crutches. In our example, the best alternative among four proposed designs, was determined by the user criterion comfort of use.